Disaster Education Learning Media for Early Childhood: A Literature Study - Dewi Hannie H. P; Zarina Akbar; Elindra Yetti (Universitas Panca Sakti Bekasi, 2023)
Various research and development of learning media related to disaster education have been carried out, such as visual learning media, graphic media, digital media, etc. However, there has been no literature review to explore disaster education learning media for early childhood. Various national and international research journal articles from Google Scholar related to disaster education learning media for early childhood during 2014—2021 will be collected and reviewed using the literature review method, namely reviewing various research journal articles. The result is known that disaster education learning media has a tendency such as: (1) trend; (2) types, especially disaster education learning media for early childhood; and (3) material and media implications for students. This research can be useful for disaster education for early childhood learning media and innovation to be ready for disaster.